Do Textbooks Matter for Reading Comprehension? A Study in Flemish Primary Education - Dockx, Jonas; Bellens, Kim; De Fraine, Bieke (Frontiers in Psychology, 2020)
This study assessed whether textbooks affect academic performance and engagement in reading comprehension in primary education in Flanders (Belgium). The data of the Progress in International Reading Literacy Study 2016 and a reassessment of this study in 2018 were used to describe students’ learning progress in reading comprehension and evolution in engagement between the fourth and sixth grade. The sample consisted of 3051 students in 98 schools. The averages of students’ learning progress and engagement were compared for five textbooks by using multilevel autoregression model and multilevel change score models. Contrasts between textbooks in average learning progress and engagement were also estimated. To control for differences between student populations that are educated with the different textbooks, we controlled for student’s socioeconomic status, language and initial academic performance in fourth grade at the student- and school-level. The main hypotheses were that textbooks affect learning progress and reading engagement. This was based on the literature and prior (mainly) cross-sectional research which describe textbooks as playing an important role in the curriculum that is taught to students on a daily basis. The results of both models showed that textbooks do not affect student’s average learning progress in reading comprehension and evolution in engagement between the fourth grade and sixth grade in Flanders. Hence, the hypotheses were rejected.